Effect of Different Drying Methods on Antioxidant Activity and Availability of Phytochemicals in Leaves of Costus speciosus, Coccinia grandis and Gymnema sylvestre - Maheshika Peries, Colombage; Navarthne, Seneviratne; Wijesinghe, Janaka; Priyashantha Henagamage, Amila; Coorey, Ranil (Asian Journal of Engineering and Applied Technology, 2022)
Drying is an important method for preserving phytochemicals in plant materials though the stability is altered with the type of drying method. This study aimed at evaluating the effectiveness of different drying methods on antioxidant activity and phytochemical availability in leaf ethanolic extracts of Costus speciosus, Coccinia grandis, and Gymnema sylvestre. Plant leaves of the selected species were subjected to shade drying at room temperature (25 + 5℃), oven drying at 45 ℃ and freeze-drying methods. The extracts were obtained by a maceration method with 95% ethanol. Obtained ethanolic extracts were analyzed for antioxidant activity in terms of 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, 2,2-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid (ABTS) radical scavenging activity, total reducing power and total antioxidant capacity. Phytochemical availability was determined qualitatively and quantitatively in the extracts. All the plant species and drying methods had a significant difference (p<0.05) for the tested antioxidant activities. Among the drying techniques, the freeze-drying method was more effective to preserve the antioxidant compounds and phytochemicals compared to oven drying and shade drying. The lowest antioxidant activity and phytochemical availability were shown by the leaves subjected to oven drying at 45 ℃. The freeze-dried leaves of C. speciosus ethanolic extract demonstrated the best radical scavenging activity for DPPH and ABTS assays with IC50 values of 57.27 + 2.08 μg/ml, 21.86+ 3.55 μg/ml respectively. Furthermore, the highest content of total phenolics (82.88+2.31 mg GAE/g), tannins (9.58 +2.71mg TAE/ g), terpenoids (45.10+3.46 %), and alkaloids (19.37+3.54%) were recorded in C. speciosus among all dried leaves from the selected species. It can be concluded that the freeze-dried leaves of all plant species showed a higher value of antioxidant activity and phytochemical availability and that can be potentially used for the production of pharmaceuticals and novel functional foods.